2021
DOI: 10.3390/molecules26123762
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Enteric Glial Cells

Abstract: Until recently, glia were considered to be a structural support for neurons, however further investigations showed that glial cells are equally as important as neurons. Among many different types of glia, enteric glial cells (EGCs) found in the gastrointestinal tract, have been significantly underestimated, but proved to play an essential role in neuroprotection, immune system modulation and many other functions. They are also said to be remarkably altered in different physiopathological conditions. A nutraceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…Although available data is scarce, some studies suggest these compounds might have antioxidant, antiinflammatory, or modulatory effects on enteric glial cells. For example, compounds like palmitoylethanolamide, cannabidiol and berberine can reduce gut inflammation and nociception in both IBD models and patients (López-Gómez et al, 2021). For the first two, these effects were described to occur through the activation of PPARs in enteric glial cells (Filippis et al, 2011;Sarnelli et al, 2018).…”
Section: Could Enteric Glial Cells Be a Therapeutic Target For Parkin...mentioning
confidence: 99%
“…Although available data is scarce, some studies suggest these compounds might have antioxidant, antiinflammatory, or modulatory effects on enteric glial cells. For example, compounds like palmitoylethanolamide, cannabidiol and berberine can reduce gut inflammation and nociception in both IBD models and patients (López-Gómez et al, 2021). For the first two, these effects were described to occur through the activation of PPARs in enteric glial cells (Filippis et al, 2011;Sarnelli et al, 2018).…”
Section: Could Enteric Glial Cells Be a Therapeutic Target For Parkin...mentioning
confidence: 99%
“…Much recent interest has been focused on the modulatory properties of EGCs for the treatment of different GI diseases, especially those characterised by chronic inflammation and altered neuroplasticity (e.g., disorders of GI hypersensitivity or motility). Most of these novel treatment strategies focus on preventing reactive gliosis 76 (reviewed in 96 ).…”
Section: Enteric Glial Cellsmentioning
confidence: 99%
“…In particular, several proteins are often used to identify EGCs, i.e., calcium-binding protein S100 [ 9 , 32 ], glial fibrillary acidic protein (GFAP) [ 9 , 33 ] and the transcription factors: SOX-8, SOX-9, SOX-10 [ 34 ] ( Figure 1 ). Interestingly, Hanani et al [ 35 ] and others [ 36 ], showed that EGCs are interconnected and electrically coupled by gap junctions and form an extensive functional glial network [ 37 ].…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%